Analysis of the Impact of Innovative Economic Conditions on the Flow of Workers in the Labour Markets of the European Union Countries - Węgrzyn, Grażyna; Salamaga, Marcin (Comparative Economic Research. Central and Eastern Europe, 2023)
The main purpose of the work is to present the results of empirical research on the impact of innovation levels in the economy on the structure of labour market flows. The analysis of the directions and scale of these flows makes it possible to discover important characteristics of the labour market and thus makes it possible to better construct and target policies to reduce unemployment or activate economically inactive people. The study uses data from the Labour Force Survey (LFS) and experimental job‑to‑job statistics for the European Union (EU) countries, covering the 2011–2019 period. We conducted research separately for selected groups of economies classified by their level of innovation, i.e. Innovation Leaders, Strong Innovators, Moderate Innovators, and Emerging Innovators. The results demonstrate that the structure of flows in a labour market depends on the innovation level of the respective economy. The main contribution of the study is that it identifies employee flow patterns in the labour markets of individual EU countries from the perspective of the innovation levels of their respective economies. Panel error correction models (ECM) and panel causality tests were used. In countries that are Innovation Leaders, an increase in participation in lifelong learning leads to a parallel increase in employee flow (EE) and job‑to‑job employee turnover. In countries that are Emerging Innovators, increasing participation in lifelong learning increases turnover, mainly among young people (15–24 age group).